The Safety of Ondansetron and Chlorpromazine for Hyperemesis Gravidarum in First Trimester Pregnancy - Şafak Özdemirci; Funda Akpınar; Melek Bilge; Funda Özdemirci; Saynur Yılmaz; Deniz Esinler; İnci Kahyaoğlu (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To evaluate the pregnancy outcome of women with nausea and vomiting of pregnancy (NVP) who were treated with either ondansetron or chlorpromazine. STUDY DESIGN: This retrospective study included 185 women who were hospitalized in the first trimester for treatment of NVP and treated with either ondansetron or chlorpromazine between January 2006 and March 2011 at Simav Government Hospital. We evaluated the pregnancy outcome including birth weight, pregnancy induced hypertension, preterm birth and major congenital malformations. RESULTS: In the ondansetron group 4 (4%) low birth weight newborn, 9 (9%) preterm birth and 1 (1%) congenital anomaly, while in chlorpromazine group 1 (1.2%) low birth weight newborn, 9 (10.6%) preterm birth and 4 (4.7%) congenital anomalies were observed. CONCLUSION: The malformation risk for both drugs found to be similar to baseline. Although the sample size was small, both drugs found to be safe to use in first trimester for NVP.